Green Banking and Sharia Compliance: Their Role in Enhancing the Financial Performance of Islamic Banks in Indonesia - Fatimah, Icha Nurul; Hadiani, Fatmi (Journal of Applied Islamic Economics and Finance, 2025)
The impetus for this research stems from the rise in the number of Islamic banks in Indonesia, which has given rise to concerns regarding the consistency of these banks' commitment to sustainable financial practices and sharia compliance. The aim of this study is to examine and assess the impact of Green Banking and Sharia Compliance on the financial performance of Islamic commercial banks in Indonesia during the period from 2020 to 2024. This study uses quantitative methods, including panel data regression analysis, and the sample consists of Islamic commercial banks registered and operating in the OJK during 2020-2024, with a total of 11 BUS. The results of the hypothesis testing show that the Profit Sharing Ratio, the Equitable Distribution Ratio and the Islamic Income Ratio have a significant effect on Return On Assets, but the Green Coin Rating and the Zakat Performance Ratio have no effect on Return On Assets.